Side chain induced weakly coordinating polyether solid state electrolyte

CN122907726APending Publication Date: 2026-10-13FUZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611258103.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-19
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

该类方法虽然可以在一定程度上提高聚合物电解质的离子传输能力,但往往依赖外加组分或物理复合结构,难以从聚合物分子链层面本征调控醚氧基团的电子性质和Li+配位环境

Benefits of technology

(1)不同于常规简单物理共混、单体自聚合及外加填料改性,本发明是通过第一类环醚单体与第二类含卤素取代侧链的环氧单体在适当引发剂条件下发生原位开环共聚,形成具有柔性链段和离子传输通道的共聚聚醚基体,并使含卤素取代侧链以共聚结构单元形式嵌入聚醚链段中,进而从分子链层面构筑侧链诱导的弱配位结构;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122907726A_ABST
    Figure CN122907726A_ABST
Patent Text Reader

Abstract

The application discloses an in-situ ring-opening copolymerization type side chain induced weak coordination polyether solid-state electrolyte, and belongs to the technical field of lithium battery solid-state electrolytes. The solid-state electrolyte comprises a copolymer polyether matrix and lithium salt dispersed therein, and the copolymer polyether matrix is formed by in-situ ring-opening copolymerization of a cyclic ether monomer as a first type of monomer and a halogen-substituted side chain-containing epoxy monomer as a second type of monomer under the action of an initiator. In the application, the halogen-substituted side chain-containing epoxy monomer is embedded into the polyether segment as a copolymer structural unit, so that the halogen-substituted side chain is located in the vicinity of the ether oxygen group, thereby reducing the electron cloud density of adjacent ether oxygen groups through a spatial adjacent induction effect, weakening the coordination between the ether oxygen group and lithium ions, and further reducing the decoordination energy barrier in the lithium ion migration process, so that the migration selectivity of lithium ions is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of lithium battery polymer solid electrolyte technology, specifically relating to a side-chain induced weakly coordinated polyether solid electrolyte. Background Technology

[0002] Solid-state lithium metal batteries are an important development direction for the next generation of high-energy-density electrochemical energy storage systems. Their commercialization process largely depends on the research and development of polymer-based solid electrolytes. Therefore, this field has received widespread attention from academia and industry in recent years.

[0003] Among various polymer solid electrolytes, polyether-based electrolytes have been extensively studied due to their good stability against lithium metal. However, the high electron cloud density of the ether oxygen groups in the polyether segments is a disadvantage for lithium ions (Li₂O₃). + Li exhibits strong coordination. This strong coordination enables Li to... + The migration process involves continuous "decoordination-recoordination," resulting in a high migration energy barrier, which limits the ionic conductivity and Li. + An increase in the number of migrations.

[0004] Existing technologies often improve ion transport performance by introducing inorganic fillers, plasticizers, pre-formed polymer matrices, or reducing polymer crystallinity. While these methods can enhance the ion transport capacity of polymer electrolytes to some extent, they often rely on added components or physical composite structures, making it difficult to intrinsically control the electronic properties of ether oxygen groups and Li at the polymer molecular chain level. + Coordination environment. Meanwhile, existing halogenated polyether or fluorinated epoxy monomer modification systems mainly focus on monomer self-polymerization, pre-made polymer matrix modification, membrane structure construction, or initiator system regulation, but have not fully solved the problem of how to directionally construct weakly coordinated structural units in polyether segments through in-situ ring-opening copolymerization between different cyclic ether monomers.

[0005] Therefore, how can we weaken the effect of ether oxygen groups on Li at the molecular chain level through comonomer structure design without relying on additional inorganic fillers or pre-fabricated polymer matrices? + The coordination effect of polyethers is a key issue in improving the ion transport performance and interfacial stability of polyether solid electrolytes. Summary of the Invention

[0006] To address the aforementioned technical problems, this invention provides an in-situ ring-opening copolymerized side-chain induced weakly coordinated polyether solid electrolyte. This electrolyte is constructed by in-situ ring-opening copolymerization of cyclic ether monomers and halogen-substituted epoxy monomers with side chains, thereby constructing side-chain induced weakly coordinated structural units in the polyether segments. This reduces the discoordination energy barrier during lithium-ion migration and effectively improves the migration selectivity of lithium ions.

[0007] To achieve the above objectives, the present invention adopts the following technical solution: A side-chain induced weakly coordinated polyether solid electrolyte comprises a copolymer polyether matrix and a lithium salt dispersed in the copolymer polyether matrix, wherein the copolymer polyether matrix is ​​formed by in-situ ring-opening copolymerization of a system comprising a first type of monomer, a second type of monomer and an initiator.

[0008] Furthermore, the first type of monomer is a cyclic ether monomer, which is used to form the polyether backbone structure.

[0009] Specifically, the first type of monomer may be selected from one or more of 1,3-dioxolane (DOL), epoxide (EO), 1,4-dioxolane (DOX), tetrahydrofuran (THF) or 2,5-dihydrofuran (DHF), preferably one or more of 1,3-dioxolane and 1,4-dioxolane.

[0010] Furthermore, the second type of monomer is an epoxy monomer containing halogen-substituted side chains that can participate in ring-opening polymerization. During in-situ ring-opening copolymerization, it is embedded in the copolymer polyether matrix as a copolymer structural unit, allowing the halogen-substituted side chains to be located adjacent to the polyether segments. The halogen-substituted side chains are substituents with negative inductive effects, which can reduce the electron cloud density of adjacent etheroxy groups through spatial proximity induction, thereby weakening the coordination interaction between the etheroxy groups and lithium ions, lowering the decoupling energy barrier during lithium ion migration, and improving lithium ion migration selectivity.

[0011] Furthermore, the halogen atom in the halogen-substituted side chain is selected from one or more of F, Cl, Br, and I.

[0012] Specifically, the second type of monomer may be selected from one or more of epifluoropropane (EFH), epichlorohydrin (ECH), epibromopropane (EBH), 2-(fluoromethyl)oxetane, 2-(chloromethyl)oxetane, 2-(bromomethyl)oxetane, 2-(iodomethyl)oxetane, 3-fluoro-1-oxetane, 3-chlorooxetane, 3-bromooxetane, 3-iodooxetane, 3-(chloromethyl)-3-methyloxetane, 3-(bromomethyl)-3-methyloxetane, 3-(iodomethyl)-3-methyloxetane, 3,3-difluoromethyl-1-oxetane, 3,3-bis(chloromethyl)oxetane, and 3,3-bis(bromomethyl)oxetane, preferably one or more of epichlorohydrin, epibromopropane, or epifluoropropane.

[0013] Furthermore, the molar ratio of the first type of monomer to the second type of monomer is 1:(0.1~2), preferably 1:(0.2~1.0). By adjusting the proportion of the second type of monomer, the density of halogen-substituted side chain structural units in the copolyether segment can be adjusted, thereby achieving the desired effect on Li. + Regulation of coordination strength and ion transport behavior.

[0014] Furthermore, the initiator is one or two of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium difluorooxalate borate (LiDFOB), aluminum trifluoromethanesulfonate (Al(OTF)3), tin trifluoromethanesulfonate (Sn(OTF)3), and tin difluoride (SnF2). These initiators not only induce the polymerization reaction in in-situ but also participate in the construction of the ion conduction network during the formation process. Some types (such as LiDFOB and SnF2) can further improve the interfacial stability between the electrolyte and the lithium metal anode.

[0015] Furthermore, the amount of the initiator is 0.05% to 2% of the total mass of the first type of monomer and the second type of monomer.

[0016] Furthermore, the lithium salt is selected from one or two of lithium bis(trifluorosulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), or lithium difluorooxalate borate (LiDFOB).

[0017] Furthermore, the amount of lithium salt used is 15% to 25% of the total mass of the first type of monomer and the second type of monomer.

[0018] The side-chain-induced weakly coordinated polyether solid electrolyte can be assembled with the positive and negative electrodes into a lithium metal battery. Specifically, it includes the following steps: (1) Mix the solvent, the first type of monomer, the second type of monomer, the initiator and the lithium salt to form an electrolyte precursor solution; (2) Weigh the positive electrode material, conductive carbon black and polyvinylidene fluoride in proportion and grind them thoroughly. Add an appropriate amount of N-methylpyrrolidone and stir evenly to obtain a slurry. Then coat it evenly on aluminum foil to obtain a positive electrode sheet. Transfer the positive electrode sheet to an oven to dry and cut it for later use. (3) Using the prepared positive electrode sheet and electrolyte precursor solution, assemble the battery in the order of positive electrode shell, positive electrode, electrolyte, separator, electrolyte, negative electrode, gasket, spring sheet and negative electrode shell; (4) The battery is heated and solidified, so that the first type of monomer and the second type of monomer in the electrolyte precursor solution undergo an in-situ ring-opening copolymerization reaction inside the battery to form a copolyether solid electrolyte containing halogen-substituted side chain copolymerization structural units.

[0019] Further, the solvent mentioned in step (1) is one of ethylene glycol dimethyl ether (DME), dimethoxymethane (DMM), 1,2-diethoxyethane (DEE), 1,2-dimethoxypropane (DMP), and diphenoxymethane (DH). All of these solvents have good electrolyte solubility and low boiling points, and can form stable and homogeneous solutions with monomers and lithium salts at room temperature, which is beneficial for achieving high ionic conductivity.

[0020] Furthermore, the cathode material mentioned in step (2) is one of lithium cobalt oxide (LCO), nickel cobalt manganese (NCM), lithium nickel cobalt aluminum oxide (NCA), or lithium iron phosphate (LiFePO4). The selected materials are representative commercial cathode systems in the current lithium battery industry, and they have good compatibility with the side-chain induced weakly coordinated polyether solid electrolyte of the present invention, proving that the weakly coordinated polyether solid electrolyte of the present invention has good universality.

[0021] Furthermore, the heating and curing temperature in step (4) is 40~120 ℃ and the time is 100~480 min.

[0022] The beneficial effects of this invention are as follows: (1) Unlike conventional simple physical blending, monomer self-polymerization and external filler modification, the present invention is to form a copolymer polyether matrix with flexible segments and ion transport channels by in-situ ring-opening copolymerization of a first type of cyclic ether monomer and a second type of epoxy monomer with halogen-substituted side chains under appropriate initiator conditions, and to embed the halogen-substituted side chains into the polyether segments in the form of copolymer structural units, thereby constructing a side chain-induced weak coordination structure at the molecular chain level; (2) This invention reduces the electron cloud density of adjacent etheroxy groups through the spatial proximity induction effect of halogen substitution side chains, thereby weakening the interaction between etheroxy groups and Li. + Coordination between them reduces Li + The decoupling energy barrier during the migration process significantly enhances ionic conductivity and Li. + Number of migrations; (3) A weak coordination environment helps to regulate Li + The deposition behavior achieves uniform lithium deposition, thereby effectively suppressing lithium dendrite growth and improving battery cycle stability and safety; (4) The present invention does not require the introduction of additional fillers. Performance optimization can be achieved simply by adjusting the structure and dosage ratio of the comonomer. The process is simple and has good compatibility with existing battery manufacturing processes. Attached Figure Description

[0023] Figure 1The figures show Fourier transform infrared (FTIR) spectra of the electrolyte precursors prepared in Example 1 and Comparative Example 1. As can be seen from the figures, compared to Comparative Example 1, the electrolyte precursor obtained in Example 1 exhibits significantly lower FTIR at 10¹¹ cm⁻¹. -1 The peak exhibits a typical COC stretching vibration peak, and this peak has undergone a red shift, which can be attributed to the electron-withdrawing effect of the -Cl group on the ether oxygen group.

[0024] Figure 2 The figures show the electrochemical impedance spectroscopy results of batteries prepared using the electrolyte precursors of Examples 1-5 and the comparative examples. As can be seen from the figures, the ionic conductivity of the batteries prepared using the polyether solid electrolytes with halogen-containing side chains in the examples is significantly improved compared to the comparative examples.

[0025] Figure 3 The graph shows the full-cell cycle performance of the batteries prepared using the electrolyte precursors of Example 1 and Comparative Example 1. As can be seen from the graph, compared to Comparative Example 1, the battery prepared using the electrolyte precursor of Example 1 still retains 92.7% of its capacity after 1200 cycles. This indicates that a weak coordination environment helps to regulate the Li... + Deposition behavior to achieve uniform lithium deposition and improve battery cycle stability. Detailed Implementation

[0026] A side-chain induced weakly coordinated polyether solid electrolyte comprises a copolymer polyether matrix and a lithium salt dispersed in the copolymer polyether matrix, wherein the copolymer polyether matrix is ​​formed by an in-situ ring-opening copolymerization reaction of a system comprising a first type of monomer, a second type of monomer and an initiator at 40-120 °C for 100-480 min.

[0027] The molar ratio of the first-type monomer to the second-type monomer is 1:(0.1~2). The amount of initiator is 0.05%~2% of the total mass of the first-type monomer and the second-type monomer. The amount of lithium salt is 15%~25% of the total mass of the first-type monomer and the second-type monomer.

[0028] The first type of monomer is a cyclic ether monomer, which may be selected from one or more of 1,3-dioxolane (DOL), epoxide (EO), 1,4-dioxolane (DOX), tetrahydrofuran (THF) or 2,5-dihydrofuran (DHF).

[0029] The second type of monomer is an epoxy monomer containing halogen-substituted side chains and capable of participating in ring-opening polymerization. It can be selected from one or more of the following: epifluoropropane (EFH), epichlorohydrin (ECH), epibromopropane (EBH), 2-(fluoromethyl)oxetane, 2-(chloromethyl)oxetane, 2-(bromomethyl)oxetane, 2-(iodomethyl)oxetane, 3-fluoro-1-oxetane, 3-chlorooxetane, 3-bromooxetane, 3-iodooxetane, 3-(chloromethyl)-3-methyloxetane, 3-(bromomethyl)-3-methyloxetane, 3-(iodomethyl)-3-methyloxetane, 3,3-difluoromethyl-1-oxetane, 3,3-bis(chloromethyl)oxetane, and 3,3-bis(bromomethyl)oxetane.

[0030] The initiator is one or two of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium difluorooxalate borate (LiDFOB), aluminum trifluoromethanesulfonate (AI(OTF)3), tin trifluoromethanesulfonate (Sn(OTF)3), and tin difluoride (SnF2).

[0031] The lithium salt is selected from one or two of lithium bis(trifluorosulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), or lithium difluorooxalate borate (LiDFOB).

[0032] To make the content of this invention easier to understand, the technical solution of this invention will be further described below with reference to specific embodiments, but this invention is not limited thereto.

[0033] Unless otherwise specified, all raw materials, reagents, instruments and equipment used in this invention can be purchased from the market or prepared by existing methods. Example 1

[0034] In a glove box, ECH (3.42 g, 0.037 mol) was added to a DME solution containing DOL (1.21 g, 0.0163 mol) (the molar ratio of DOL to DME was 2:1), and the mixture was ultrasonically dispersed for 30 min to obtain a homogeneous dispersion. Subsequently, LiTFSI (0.861 g, 0.003 mol) and initiator LiDFOB (28.8 mg, 0.0002 mol) were added, and the mixture was magnetically stirred at room temperature for 60 min to obtain a homogeneous electrolyte precursor solution. Example 2

[0035] Replace the ECH used in Example 1 with an equimolar amount of EBH, and perform the remaining operations as in Example 1. Example 3

[0036] Replace the ECH used in Example 1 with an equimolar amount of EFH, and perform the other operations as in Example 1. Example 4

[0037] Replace the molar ratio of DOL to ECH in Example 1 with 1:1, and perform the remaining operations as in Example 1. Example 5

[0038] Replace ECH in Example 1 with an equimolar mixture of ECH and EBH (molar ratio 1:1), and perform the remaining operations as in Example 1.

[0039] Comparative Example 1 Epichlorohydrin was not added during the operation, and the rest of the operation was the same as in Example 1.

[0040] Comparative Example 2 In Example 2, ECH was replaced with an equimolar amount of propylene oxide (PO) that does not have an electron-withdrawing effect, and the rest of the operation was the same as in Example 1.

[0041] The electrolyte precursor solutions obtained in the examples and comparative examples were used to prepare batteries using the following method, and the ionic conductivity and Li were tested. + Performance testing of migration count: 1) Mix LiFePO4, Super P and PVDF in a mass ratio of 8:1:1, add an appropriate amount of N-methylpyrrolidone and stir to form a uniform slurry, coat it evenly on the surface of aluminum foil, dry it and cut it into a 10 mm diameter disc as the positive electrode; 2) Assemble the CR2032 coin cell in the following order: positive electrode shell, positive electrode, electrolyte, separator, electrolyte, lithium metal sheet, gasket, spring sheet, and negative electrode shell. 3) The assembled battery is heated at 65 °C for 240 min to allow the monomers to undergo in-situ ring-opening polymerization and form a solid electrolyte.

[0042] Table 1

[0043] As shown in Table 1, compared with Comparative Example 1 which does not contain the second type of monomer, the battery prepared using the solid polymer electrolyte with the second type of epoxy monomer introduced in the example has a higher room temperature ionic conductivity and Li... + The migration numbers were significantly improved. Compared to Comparative Example 2, which used the non-electron-withdrawing side-chain monomer PO, the battery prepared using the halogen-containing side-chain copolyether solid electrolyte of Example Example also exhibited higher ionic conductivity and Li... + The migration number indicates that its performance improvement is not solely due to the introduction of comonomers or the dilution effect of polymer segments, but rather to the influence of halogen-containing side-chain copolymer structural units on adjacent ether oxygen sites (Li). +It is closely related to the targeted regulation of the coordination environment.

[0044] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit them. Equivalent substitutions, modifications, or improvements made by those skilled in the art to the technical solutions of the present invention without departing from the inventive concept should all fall within the protection scope of the present invention.

Claims

1. A side-chain-induced weakly coordinated polyether solid electrolyte, comprising a copolyether matrix and a lithium salt dispersed in the copolyether matrix, characterized in that, The copolymer polyether matrix is ​​formed by in-situ ring-opening copolymerization of a system containing a first type of monomer, a second type of monomer, and an initiator.

2. The side-chain-induced weakly coordinated polyether solid electrolyte according to claim 1, characterized in that, The first type of monomer is a cyclic ether monomer.

3. The side-chain-induced weakly coordinated polyether solid electrolyte according to claim 1 or 2, characterized in that, The first type of monomer is selected from one or more of 1,3-dioxolane, epoxide, 1,4-dioxolane, tetrahydrofuran, or 2,5-dihydrofuran.

4. The side-chain-induced weakly coordinated polyether solid electrolyte according to claim 1, characterized in that, The second type of monomer is an epoxy monomer containing halogen-substituted side chains and capable of participating in ring-opening polymerization.

5. The side-chain-induced weakly coordinated polyether solid electrolyte according to claim 1 or 4, characterized in that, The second type of monomer is selected from one or more of the following: epifluoropropane, epichlorohydrin, epibromopropane, 2-(fluoromethyl)oxetane, 2-(chloromethyl)oxetane, 2-(bromomethyl)oxetane, 2-(iodomethyl)oxetane, 3-fluoro-1-oxetane, 3-chlorooxetane, 3-bromooxetane, 3-iodooxetane, 3-(chloromethyl)-3-methyloxetane, 3-(bromomethyl)-3-methyloxetane, 3-(iodomethyl)-3-methyloxetane, 3,3-difluoromethyl-1-oxetane, 3,3-bis(chloromethyl)oxetane, and 3,3-bis(bromomethyl)oxetane.

6. The side-chain-induced weakly coordinated polyether solid electrolyte according to claim 1, characterized in that, The molar ratio of the first type of monomer to the second type of monomer used is 1:(0.1~2).

7. The side-chain-induced weakly coordinated polyether solid electrolyte according to claim 1, characterized in that, The initiator is one or two of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium difluorooxalate borate, aluminum trifluoromethanesulfonate, tin trifluoromethanesulfonate, and tin difluoride, and its amount is 0.05% to 2% of the total mass of the first type monomer and the second type monomer.

8. The side-chain-induced weakly coordinated polyether solid electrolyte according to claim 1, characterized in that, The in-situ ring-opening copolymerization is carried out at a temperature of 40~120 ℃ for a time of 100~480 min.

9. The side-chain-induced weakly coordinated polyether solid electrolyte according to claim 1, characterized in that, The lithium salt is selected from one or two of lithium bis(trifluorosulfonyl)imide, lithium bis(fluorosulfonyl)imide, or lithium difluorooxalate borate, and its amount is 15% to 25% of the total mass of the first type monomer and the second type monomer.

10. A lithium metal battery assembled using the side-chain-induced weakly coordinated polyether solid electrolyte of claim 1.